Benefits of Bifidobacterium animalis subsp. lactis Probiotic in Experimental Periodontitis. Issue 2 (1st February 2017) - Oliveira, Luiz F.F.; Salvador, Sérgio L.; Silva, Pedro H.F.; Furlaneto, Flávia A.C.; Figueiredo, Luciene; Casarin, Renato; Ervolino, Edilson; Palioto, Daniela B.; Souza, Sérgio L.S.; Taba, Mario; Novaes, Arthur B.; Messora, Michel R.
Abstract : Background: This study evaluates effects of topical administration of probiotic bacteria of the genus Bifidobacterium on experimental periodontitis (EP) in rats. Methods: Thirty‐two rats were divided into groups C (control; without EP), EP (EP only), C‐HN019 (control+probiotic), and EP‐HN019 (EP+probiotic). On day 0 of the experiment, animals of groups EP and EP‐HN019 received cotton ligatures around mandibular first molars (MFMs). In groups C‐HN019 and EP‐HN019, 1 mL of suspensions containing Bifidobacterium animalis subsp. lactis ( B. lactis ) HN019 was topically administered in the subgingival region of MFMs on days 0, 3, and 7. In groups C and EP, topical administrations were performed using a sham suspension (without probiotic). All animals were euthanized at day 14. Gingival tissue, hemimandibles, and oral biofilm were collected. Data were statistically analyzed ( P <0.05). Results: Group EP presented greater bone porosity, trabecular separation, and connective tissue attachment loss (CTAL) as well as reduced bone volume than all other groups ( P <0.05). In group EP‐HN019, there were greater proportions of Actinomyces and Streptococcus ‐like species and lower proportions of Veillonella parvula, Capnocytophaga sputigena, Eikenella corrodens, and Prevotella intermedia ‐like species than group EP. Group EP‐HN019 presented greater expressions of osteoprotegerin and β‐defensins than group EP ( P <0.05). Group EP presented greater levels of interleukin‐1β and receptor activator of nuclear factor‐kappa B ligand than group EP‐HN019 ( P <0.05). Conclusion: Topical use of B. lactis HN019 promotes a protective effect against alveolar bone loss and CTALs attributable to EP in rats, modifying immunoinflammatory and microbiologic parameters.